2005
DOI: 10.4049/jimmunol.175.5.2968
|View full text |Cite
|
Sign up to set email alerts
|

EBV Infection of Human B Lymphocytes Leads to Down-Regulation of Bim Expression: Relationship to Resistance to Apoptosis

Abstract: EBV infects a large proportion of the human population worldwide and is one of the major viruses with human B lymphocyte tropism. It can immortalize human B lymphocytes and controls their resistance to apoptosis. EBV infection is associated with several lymphomas, including Burkitt’s lymphoma. In this report we show that EBV infection leads to the post-transcriptional down-regulation of expression of the proapoptotic protein Bim. This process involves the phosphorylation of BimEL by the constitutive EBV-activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Phosphorylation of BIM by ERK was reported to be critical for the antiapoptotic activity of this kinase. [56][57][58][59][60] However, a recent study has shown that ERK-mediated direct phosphorylation of BIM does not have a major role in the control of the proapoptotic activity of this BH3-only protein within the whole animal. 61 Both BIM and BMF were shown to be sequestered by binding to elements of the cytoskeleton, thereby restraining their pro-apoptotic activity.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%
“…Phosphorylation of BIM by ERK was reported to be critical for the antiapoptotic activity of this kinase. [56][57][58][59][60] However, a recent study has shown that ERK-mediated direct phosphorylation of BIM does not have a major role in the control of the proapoptotic activity of this BH3-only protein within the whole animal. 61 Both BIM and BMF were shown to be sequestered by binding to elements of the cytoskeleton, thereby restraining their pro-apoptotic activity.…”
Section: The Bcl-2-regulated Apoptotic Pathwaymentioning
confidence: 99%
“…Bim is also particularly important in the regulation of apoptosis during B-cell development, and its regulation by cMyc can play an important role in the pathogenesis of BL (8,11,26). Furthermore, a recent report indicated that EBV-converted BL41 and Ramos cells express lower levels of Bim than the parental lines (7). Protein extracts from the matched pairs of EBVϪve and EBVϩve cells previously screened for caspase activity were analyzed by Western blotting and probed for expression of the Bim proteins (Fig.…”
Section: Vol 81 2007 Ebv-induced Resistance To Microtubule-disruptimentioning
confidence: 99%
“…16 To test the biological function of SPRY2 W119 variant, we investigated the MAPK/ERK pathway by western blot in the available cell lines. Because in EBV-transformed B lymphoblasts the ERK1/2 pathway is constitutively active, 17 the level of phosphoERK1/2 (pERK1/2) was directly analyzed. pERK1/2 was hypophosphorylated in all mutation carriers as well as in the LCL156 and LCL157, compared with the control cell lines and to IV-46, negative for SPRY2 mutations (Figures 3a and b).…”
Section: Exome Sequencing and Bioinformatics Analysismentioning
confidence: 99%